Muslim female athletes in sports and dress code: major obstacle in international competitions - Qureshi, Yasmeen Iqbal; Ghouri, Soniha Aslam (Journal of Experimental Sciences, 2011)
Sport and physical activities in Muslim nations are believed to be male dominated institution and girls often confronted with considerable challenges, deprived them from taking part in International competitions and Olympics Games. Prohibition is mainly because of dress code and some restrictions laid down in religion, for which Muslim nations don’t allow their girls to compete in International and Olympic games. Under these alarming conditions attempt has been made to address those issues faced by Muslim girls in sports competitions and to find out the middle course acceptable to western and Muslim nations’ sports organizations influencing governments to encourage girls’ participation in International sports competitions. In near future, it is hoped that scholars will conduct further research on this important topic. It is just an initial opening of this difficult and delicate subject to elaborate it for the convenience both conflicting nations world over.